Low warping and high toughness recycled high density polyethylene for fused filament fabrication 3D printing - Gopal, Animesh; Chaubal, Aman; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2026)
The incorporation of recycled polymers in additive manufacturing offers a sustainable pathway to reduce plastic waste while enabling cost-effective production of functional components. High-density polyethylene (HDPE) is an attractive material for 3D printing owing to its low density, chemical resistance, and recyclability. However, its high crystallinity and tendency to shrink often lead to warpage and poor interlayer adhesion. This study proposes a blend-based strategy to overcome these limitations by incorporating tough linear low-density polyethylene (LLDPE) into recycled HDPE (rHDPE). The blends were prepared through melt extrusion, and their mechanical, rheological, morphological, and thermal properties, and 3D printability were comprehensively evaluated. rHDPE/LLDPE blends showed a remarkable improvement in elongation at break (from 3.2% to 84.7%) and toughness without compromising tensile strength. Addition of LLDPE led to a moderate reduction in the crystallinity of rHDPE/LLDPE blends (from 69% to 52.5%) but a significant reduction in the warpage of 3D printed samples (from 27% to 7.6%). Rheological and morphological analyses confirmed good miscibility and uniform phase distribution in the blends, with increasing LLDPE content enhancing complex viscosity and melt elasticity. Overall, the rHDPE/LLDPE blends exhibit superior mechanical performance and reduced warpage, establishing their potential for FFF 3D printing applications.
Keywords: Crystallization; FFF 3D printing; high-density polyethylene blends; Recycling; toughness; warpage